Characterization of Soybean Protein Hydrolysates able to Promote the Proliferation of Streptococcus Thermophilus ST. Issue 4 (12th March 2013) - Hongfei, Zhao; Fengling, Bai; Fang, Zhou; Walczak, Piotr; Xiangning, Jiang; Bolin, Zhang
Abstract How soybean protein hydrolysates (SPHs) to favor the growth of S. thermophilus ST were investigated. Hydrolyzed soybean protein was fractionated to 4 fragments, that is, SPH‐I, SPH‐II, SPH‐III, and SPH‐IV according to their molecular weight sizes. SPHs can improve the growth of strain ST, in which SPH‐IV, with the molecular weight of less than 5 kD, significantly promoted the growth of strain ST. The cell counts of strain ST grew quickly from 7.71 to 9.78 (log CFU/mL) when the concentrations of SPH‐IV ranging from 0% to 1%. Moreover, 2 chemically defined media (CDMs) were used to test their roles in maintaining the viability of strain ST. CDMs only maintained the survival of strain ST, but SPH‐IV had the promotional effects on proliferation of the bacteria. SPH‐IV was further characterized to be oligopeptides that contain 2 to 8 amino acids and free amino acids by high‐performance liquid chromatography—mass spectrometry (HPLC‐MS) analysis. The amino acid compositions showed that SPH‐IV contained more essential amino acids, which were necessary for the growth of S. thermophilus ST. Clearly, SPH‐IV could be used as an exogenous nitrogen supplement to enhance the proliferation of S. thermophilus ST and other lactic acid bacteria, and the data from small scale‐up fermentation also supported this point.